2021
DOI: 10.29140/jaltcall.v17n2.378
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating E-portfolio with flipped classrooms: An in-depth analysis of students’ speaking performance and learning engagement

Abstract: The advent of technology has enabled the implementation of e-portfolio in students speaking performance to collect and store their artifacts online. With the implementation of technology, e-portfolio tends to be incorporated with flipped classrooms. Previous studies, however, failed to consider the implementation of this incorporation, especially in teaching speaking skills. it is thereby leading to a lack of literature on this topic. This research, therefore, aims to examine the effect of e-portfolio in flipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…According to Caner ( 2010 ) and Chappuis ( 2014 ), successful learner engagement depends on how well L2 learners understand the goals pronounced in writing PA, how soon they picture the distance between their status quo and those goals, and what they do to achieve the goals. In the same vein, L2 writing teachers are recommended to prime self-reflectiveness through ‘scaffolding’ the students in terms of tutorials to the entire PA process (Carless and Boud, 2018 ; Kusuma et al 2021 ), using examples and prompts (Gregory et al, 2001 ), extending deadlines to engage students even more (Lam, 2014 ), and informing them of the assessment rubrics (Panadero and Romero, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to Caner ( 2010 ) and Chappuis ( 2014 ), successful learner engagement depends on how well L2 learners understand the goals pronounced in writing PA, how soon they picture the distance between their status quo and those goals, and what they do to achieve the goals. In the same vein, L2 writing teachers are recommended to prime self-reflectiveness through ‘scaffolding’ the students in terms of tutorials to the entire PA process (Carless and Boud, 2018 ; Kusuma et al 2021 ), using examples and prompts (Gregory et al, 2001 ), extending deadlines to engage students even more (Lam, 2014 ), and informing them of the assessment rubrics (Panadero and Romero, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The findings suggest that high levels of interaction positively influence positive collaborative learning and engagement, which improves student performance. Kusuma et al [7] obtained data from 63 Grade 12 students, where 29 students are in the experimental group and 34 students are in the control group, defining student engagement as including behavioral, cognitive, and emotional involvement. Bergdahl et al [8] concluded that high-performing students developed strategies to use digital technology in a supportive and productive manner.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…E-portfolios have in fact been deemed one of 34 innovative approaches to teaching in higher education [15] and one of 11 high-impact practices that have the greatest influence on students' learning, comprehension, and engagement [16]. Despite having been used in education for decades with well-documented benefits, few studies have provided empirical evidence on how to implement e-portfolios in the classroom [17]- [19].…”
Section: Introductionmentioning
confidence: 99%